N-[4-(Dimethylamino)benzylidene]-3,4-dimethylisoxazol-5-amine - Tan, Kong Wai; Ng, S.W.; Asiri, A.M.; Khan, S.A. (International Union of Crystallography, 2010)
The aromatic rings attached to the azomethine double bond in the title compound, C(14)H(17)N(3)O, are trans to each other [C-C=N-C torsion angle = 179.5 (1)degrees], and they are approximately coplanar [dihedral angle between the five-and six-membered rings = 13.7 (1)degrees].